Perceived importance and understanding of collection development policy amongst academic librarians in Nigeria / Buhari Yakubu - Buhari , Yakubu (2021)
Despite the importance of collection development policy (CDP) in developing library collection, little has been written about the perception and knowledge of those who are responsible for formulating, maintaining, and updating this policy, especially in Nigeria where collection development challenges seem to be rampant. The objective of this study was to assess the perceived importance and understanding of collection development policy among academic librarians in Nigeria. The study employed a quantitative methodology using a survey research design. A survey questionnaire developed based on the IFLA (2001) guideline for the collection development policy was used to collect the data for this study. One hundred and thirty-six (I36) academic librarians were recruited from three selected academic libraries in the Northwestern zone of Nigeria using a stratified sampling method. Data were analyzed using descriptive and correlational analysis. The findings revealed that academic librarians had a high perceived importance and understanding level of CDP. The findings also revealed that educational level had a statistically significant correlation with the perceived importance (p = .000) and understanding of CDP (p = .009). However, the working experience had no statistically significant correlation with the perceived importance (p = .100) and understanding of CDP (p = .307). This study has contributed to the management of academic libraries by providing useful and reliable information on the perceived importance and understanding level of CDP among academic librarians in Nigeria. The study recommends that various educational programs should be developed to provide a better perception and understanding of CDP among library professionals in Nigeria.